YOGA ASASANAS PRACTICE TO IMPROVE FLEXIBILITY IN EARLY CHILDREN - Ni Putu Indriani (JARITA : Journal of Children’s Education and Learning Research, 2023)
Early childhood is said to be in the golden age. This period is a period where children grow and develop very rapidly, both physically and psychologically. Flexibility is one of the components of physical condition that has an important role, including supporting activities of daily activities. Asana is a state of the body in a steady state, calm, relaxed, and comfortable both physically and mentally (Sarasvati, 2002). For children who are in their infancy, yoga asana is very good to do because it trains physically and mentally holistically where yoga affects the function of the nervous system, endocrine glands, all organs can be involved in it including muscles, bones, nerves, glands, roads. respiratory, exhaust and circulatory system as appropriate. Yoga movements are also believed to bring joy to children. This article uses qualitative research methods with literature studies or literature studies that examine the practice of yoga asanas to increase flexibility in early childhood. Yoga helps children build flexibility strength by training flexibility in both weak and stiff children.